Modern Approaches and Perspectives of Human Cord Blood Nucleated Cells’ Freeze-Drying - Goltsev, Anatoliy; Lutsenko, Olena; Ostankova, Lyudmyla; Bondarovych, Mykola; Ostankov, Maksym; Sokil, Larysa; Hrisha, Igor; Chernyshenko, Lyudmyla (Problems of Cryobiology and Cryomedicine, 2024)
The review summarizes data on the prospects of using lyophilization as a methodical approach to preserve structure and functions for a long-term storage of human cord blood leukoconcentrate (HCBL). The advantages of the freeze-drying compared to low-temperature storage, natural or thermal drying have been shown. The question of the impact of physical and chemical factors, which are implemented at the stage of lyophilization, on structure and functions of HCBL cells has been considered. The importance of such factors as cell concentration, storage conditions, residual moisture in ensuring the preservation of lyophilized material was disputed. The paper analyzes the data on the use of lyoprotectants and antioxidants during freeze-drying as well as discusses the safety of using lyoprotectant delivery methods in relation to the genomic profile of cells. Probl Cryobiol Cryomed 2023; 33(4): 227–249